Use of a two-dimensional pseudo-homogeneous model for the study of temperature and conversion profiles during a polymerization reaction in a tubular chemical reactor - Marghsi, Mohamed (Materiali in tehnologije, 2012)
A two-dimensional pseudo-homogeneous model is used to study temperature and conversion profiles during the polymerization reaction of low-density polyethylene (LDPE) in a tubular chemical reactor. This model is integrated with the Runge-Kutta 4th-order semi-implicit method, using orthogonal collocation to transform a system of complex equations into the ordinary differential ones, with respect to the heat and mass transfers involved. Ethylene polymerization has been simulated over a range of temperatures and pressures and according to the mechanisms of radical polymerization. The results of several tests, carried out under the conditions similar to those of an industrial-scale polymerization, are presented. The influences of the initial temperature Tsub0, the total pressure Psubt and the ratio L/D (the main dimensions of the reactor) on the profiles of the temperature and conversion rates are tested and analyzed to predict the behavior and performance of the tubular chemical reactor considered. The focus was on the effect of an increase in the initial temperature Tsub0 since such a rise results in a decrease in Tsubc (hot spot) appearing at the entrance of the reactor on the one hand, and in an improved conversion on the other hand. An opposite effect is observed for Psubt since a pressure increase will result in a rapid rise in Tsubc and a decrease in the conversion. The ranges of pressures and temperatures are thus limited by the system performance: excessive pressures must be avoided and working temperatures must be chosen in the range where the polymerization reaction is very fast; such conditions allow not only a good conversion, but also a resulting polymer with a low crystallinity and, thus, alow density. In the present work the effect of the L/D ratio was also studied in order to find the most suitable ratio that permits the best evacuation of the heat released during the polymerization.
Keywords: chemical kinetics; kemijska kinetika; modeling; modeliranje; cevast reaktor; tubular reactor; simulacija; simulation; polimerizacija; polymerization; polyethylene; polietilen; pseudo-homogeneous two-dimensional model; psevdohomogen dvodimenzionalni model